STRATEGI PEMBELAJARAN QURAN HADIS DALAM MEMAKSIMALKAN PROSES PEMBELAJARAN ALQURAN HADIS - Zulkipli Nasution (STIT Al-Ittihadiyah Labuhanbatu Utara, 2020)
Choosing the right teaching and learning strategy is very important in the learning process. The learning strategy consists of all components of learning material and procedures or stages of learning activities used by educators in order to help students achieve certain learning objectives. The learning strategy is an action plan including the use of methods and the use of various resources in learning, strategies are formulated to achieve certain goals. The learning material of the Qur'an Hadith has a more dominant affective domain, so that when learning this material takes place without touching the affective domain, it can be ascertained that the learning objectives are not achieved optimally. There are various kinds of learning methods and techniques that will be used by educators, but not all of them are equally effective in achieving learning goals. This requires the creation and innovation of teachers in choosing strategies. Learning the Koran Hadith which is an important part of Islamic education also contributes to the achievement of national education. Learning Al-Quran Hadith is the provision of knowledge or reading skills from educators to students so that students can have knowledge and skills about the Qur'an Hadith.